2010
DOI: 10.1007/s10725-010-9498-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of aeroponics to investigate antioxidant activity in the roots of Xerophyta viscosa

Abstract: In order to ultimately understand the whole plant mechanism of attaining desiccation tolerance, we undertook to investigate the root tissues of the resurrection plant Xerophyta viscosa, as previous work has only been conducted on the leaf tissues of resurrection plants. An aeroponic plant growth system was designed and optimised to observe the root's response to desiccation without the restrictions of a soil medium, allowing easy access to roots. Successful culture of both X.viscosa and the control, Zea mays, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…It has shown that transcription of a recently discovered gene encoding an enzyme essential to ascorbic acid biosynthesis, in the resurrection plant X. viscosa, is upregulated when the plants are dried below 60% relative water content and that mRNA levels remain high in the desiccated plant and during early stages of rehydration. Ascorbate levels in roots and leaves of this plant follow the same trend [46] and we propose that elevated ascorbate levels are maintained during drying and early rehydration by a combination of de novo synthesis and regeneration of ascorbate [14,46]. Further to the standard housekeeping antioxidants, resurrection plants have the ability to induce, de novo, antioxidants such as 1-and 2-cys-peroxiredoxins, glyoxylase I family proteins, and zinc metallothionine and metallothionine-like antioxidants in response to desiccation [14,34,47,48].…”
Section: Modulating Antioxidants and Associated Metabolismsupporting
confidence: 54%
“…It has shown that transcription of a recently discovered gene encoding an enzyme essential to ascorbic acid biosynthesis, in the resurrection plant X. viscosa, is upregulated when the plants are dried below 60% relative water content and that mRNA levels remain high in the desiccated plant and during early stages of rehydration. Ascorbate levels in roots and leaves of this plant follow the same trend [46] and we propose that elevated ascorbate levels are maintained during drying and early rehydration by a combination of de novo synthesis and regeneration of ascorbate [14,46]. Further to the standard housekeeping antioxidants, resurrection plants have the ability to induce, de novo, antioxidants such as 1-and 2-cys-peroxiredoxins, glyoxylase I family proteins, and zinc metallothionine and metallothionine-like antioxidants in response to desiccation [14,34,47,48].…”
Section: Modulating Antioxidants and Associated Metabolismsupporting
confidence: 54%
“…However, the plant grows speedily in the system due to the sterile environment and abundant oxygen availability in the growth chamber. However, several research studies practiced the modern plant growing technology for the cultivation of horticultural ornamental, the root of herbs and root based medicinal plants production (Clayton and Lamberton 1964;Cho et al 1996;Park and Chiang 1997;Burgess et al 1998;Garrido et al 1998a;Garrido et al 1998b;Scoggins and Mills 1998;Molitor et al 1999;Kamies et al 2010). Stoner (1983) reported that before 1966s the aeroponics system was performed only as a laboratory analysis to investigate the plant root structure.…”
Section: Overview and Concept Of The Aeroponics Systemmentioning
confidence: 99%
“…Typically such studies pose specific research questions and are conducted using discipline specific approaches on a single species, but often reflect some common questions and strategies associated with research into desiccation tolerance. Papers within this issue report on stresses associated with water deficit, such as the mechanical stress of plasmolysis (Koster et al 2010), oxidative stresses, including those associated with light (Aidar et al 2010;Proctor 2010;Kamies et al 2010;Colville and Kranner 2010) and the protective responses generated in response to those stresses, or take a more global approach of searching for genes and gene products up regulated in response to stress (Abdalla et al 2010). In addition to furthering our understanding of stresses and associated protection these works add important information to the field.…”
mentioning
confidence: 99%
“…Proctor (2010) utilizes chlorophyll-fluorescence parameters to compare and quantify recovery responses in a range of bryophytes and pteridophytes and proposes that this tool can give insight into factors influencing recovery time and rate. Kamies et al (2010) describe the successful use of aeroponics to study antioxidant responses of roots of the resurrection plant Xerophyta viscosa to desiccation. There are few studies reported on roots of resurrection plants largely due to the problems associated with adherence of soil and associated microbes which cannot be removed from dry roots without altering tissue water content.…”
mentioning
confidence: 99%
See 1 more Smart Citation